2019
DOI: 10.1049/htl.2018.5034
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localisation of hesitant steps in people with Alzheimer's disease navigating routes of varying complexity

Abstract: People with Alzheimer's disease (AD) have characteristic problems navigating everyday environments. While patients may exhibit abnormal gait parameters, adaptive gait irregularities when navigating environments are little explored or understood. The aim of this study was to assess adaptive locomotor responses of AD subjects in a complex environment requiring spatial navigation. A controlled environment of three corridors was set up: straight (I), U-shaped (U) and dog-leg (S). Participants were asked to walk al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Disproportionately long step times were considered to represent hesitations, consistent with previous observational 1,4 and gait investigations 35 . Individual step times were calculated using threshold resultant acceleration values detecting when the foot was in contact with the floor.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Disproportionately long step times were considered to represent hesitations, consistent with previous observational 1,4 and gait investigations 35 . Individual step times were calculated using threshold resultant acceleration values detecting when the foot was in contact with the floor.…”
Section: Methodsmentioning
confidence: 99%
“…Medians of observed person‐specific median step times were calculated for each group, combining data from all trials irrespective of shadow condition. Outlying long step times were iteratively identified as follows 35 . For each of the three groups, a three‐level linear mixed model was fitted including random effects for participant, “room condition within participant,” and “trial within participant and room condition.” Outliers with long step times were defined as observations with a standardized residual >3; these were removed, the model refitted, and outlier removal repeated until no further outliers were identified.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous lab-based research has demonstrated differences in gait parameters such as step-time and walking speed between people with dementia and age-matched controls (Marquis et al, 2002;Waite et al, 2005;Wang et al, 2006;Verghese et al, 2007;Cedervall et al, 2014;Rosso et al, 2017). These studies indicate that the decline is linked to both phenotype and stage of the disease (Allali et al, 2016;Castrillo et al, 2016;Del Campo et al, 2016;McCarthy et al, 2019;Yong et al, 2020). Furthermore, a noticeable decline in gait is thought to predate other cognitive decline (Hall et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…People with typical Alzheimer's Disease (tAD) have characteristic issues when navigating their everyday environments (McCarthy et al, 2019) with a noticeable general decline in gait patterns (Valkanova and Ebmeier, 2017). Previous lab-based research has demonstrated differences in gait parameters such as step-time and walking speed between people with dementia and age-matched controls (Marquis et al, 2002;Waite et al, 2005;Wang et al, 2006;Verghese et al, 2007;Cedervall et al, 2014;Rosso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%